1998
DOI: 10.1084/jem.187.8.1215
|View full text |Cite
|
Sign up to set email alerts
|

Aminooxypentane-RANTES Induces CCR5 Internalization but Inhibits Recycling: A Novel Inhibitory Mechanism of HIV Infectivity

Abstract: CCR5, a chemokine receptor expressed on T cells and macrophages, is the principal coreceptor for M-tropic HIV-1 strains. Recently, we described an NH2-terminal modification of the CCR5 ligand regulated on activation, normal T cell expressed and secreted (RANTES), aminooxypentane-RANTES (AOP-RANTES), that showed potent inhibition of macrophage infection by HIV-1 under conditions where RANTES was barely effective. To investigate the mechanism of AOP-RANTES inhibition of HIV infectivity we examined the surface ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
362
6
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 386 publications
(393 citation statements)
references
References 37 publications
22
362
6
3
Order By: Relevance
“…Agonist treatment induced reduction of high expressers, rather than quantitative loss of CCR5 on all these cells ( Figure 1A1). In agreement with earlier reports (Mack et al, 1998), the IC 50 and t 1/2 for AOP-RANTES was at least threefold better than for RANTES or MIP-1␤. …”
supporting
confidence: 81%
See 2 more Smart Citations
“…Agonist treatment induced reduction of high expressers, rather than quantitative loss of CCR5 on all these cells ( Figure 1A1). In agreement with earlier reports (Mack et al, 1998), the IC 50 and t 1/2 for AOP-RANTES was at least threefold better than for RANTES or MIP-1␤. …”
supporting
confidence: 81%
“…Likewise, agonist occupied CXCR4 underwent clathrindependent endocytosis in both primary cells and ectopic expression systems (Amara et al, 1997). Although these studies implied that agonist-driven endocytosis of CCR5 followed the clathrin pathway, a recent report suggested that CCR5 endocytosis followed both clathrin-and caveolae-dependent routes in CHO and HeLa cells (Mueller et al, 2002).Although previous studies (Amara et al, 1997;Mack et al, 1998) examined the rate and route of CCR5 and CXCR4 internalization in both T cells and stable cell lines, there has not been a quantitative head-to-head comparison of the two. Moreover, their localization to specific plasma membrane domains has not been clearly defined.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Chemokine activation of these intracellular signals is often accompanied by chemokine receptor internalization and trafficking back to the cell membrane. The intracellular trafficking of chemokine receptors controls their activities, and the balance between the chemokine receptor recycling and degradation dictates the leukocyte responsiveness to chemokines (Sabroe et al, 1997;Asagoe et al, 1998;Khandaker et al, 1998;Mack et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Chemokine activation of these intracellular signals is often accompanied by chemokine receptor internalization and trafficking back to the cell membrane. The intracellular trafficking of chemokine receptors controls their activities, and the balance between the chemokine receptor recycling and degradation dictates the leukocyte responsiveness to chemokines (Sabroe et al, 1997;Asagoe et al, 1998;Khandaker et al, 1998;Mack et al, 1998).Ligand stimulated chemokine receptor internalization can be accomplished through the formation of clathrin-coated pits and/or through formation of lipid rafts (Signoret et al, 1997;Yang et al, 1999;Mueller et al, 2002;Venkatesan et al, 2003). The coated pits internalize as coated vesicles and the later fuse to early endosomes after uncoating (Wu et al, 2001).…”
mentioning
confidence: 99%